2021
DOI: 10.1071/fp21148
|View full text |Cite
|
Sign up to set email alerts
|

Proteome changes and associated physiological roles in chickpea (

Abstract: Interrogative proteome analyses are used to identify and quantify the expression of proteins involved in heat tolerance and to identify associated physiological processes in heat-stressed plants. The objectives of the study were to identify and quantify the expression of proteins involved in heat tolerance and to identify associated physiological processes in chickpea (Cicer arietinum L.) heat-tolerant (Acc#7) and sensitive genotype (Acc#8) from a field study. Proteomic and gene ontological analyses showed an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Through this analysis, they uncovered several candidate genes associated with thermotolerance. Similarly, Makonya et al [221] investigated heat stress and found that the heat-tolerant genotypes exhibited an increase in specific proteins related to protein synthesis, defense, and transport during the flowering stage. These proteins included sucrose-phosphate synthase, sucrose-phosphatase, HSP70, ribulose bisphosphate carboxylase/oxygenase activase, plastocyanin, and protoporphyrinogen oxidase.…”
Section: Omics-based Technology and Transgenesis Approach For Drought...mentioning
confidence: 99%
“…Through this analysis, they uncovered several candidate genes associated with thermotolerance. Similarly, Makonya et al [221] investigated heat stress and found that the heat-tolerant genotypes exhibited an increase in specific proteins related to protein synthesis, defense, and transport during the flowering stage. These proteins included sucrose-phosphate synthase, sucrose-phosphatase, HSP70, ribulose bisphosphate carboxylase/oxygenase activase, plastocyanin, and protoporphyrinogen oxidase.…”
Section: Omics-based Technology and Transgenesis Approach For Drought...mentioning
confidence: 99%
“…In a study on Monterey pine ( Pinus radiata ) embryos exposed to two HS conditions (40°C for 4 h, 60°C for 5 min), proteomic analysis revealed the up‐regulation of ribosomes, cell wall carbohydrates, transmembrane transport proteins, HSPs and chaperones, post‐transcriptional regulation proteins, and fatty acid biosynthesis proteins and the down‐regulation of adenosylhomocysteinase protein, glycolytic pathway enzymes, nitrogen assimilation enzymes, oxidative stress enzymes, and methionine‐tRNA ligase (Castander‐Olarieta et al, 2021). Similarly, in chickpea ( Cicer arietinum L.), HS led to the differential expression of various proteins, including HSP70, ribulose bisphosphate carboxylase/oxygenase activase, plastocyanin oxidase and protoporphyrinogen oxidase, alongside the up‐regulation of proteins related to defense, transport, intracellular traffic, and protein biosynthesis (Makonya et al, 2021).…”
Section: Omics‐driven Breeding For Temperature‐smart Plantsmentioning
confidence: 99%
“…40 C for 4 h, 60 C for 5 min), proteomic analysis revealed the upregulation of ribosomes, cell wall carbohydrates, transmembrane transport proteins, HSPs and chaperones, post-transcriptional regulation proteins, and fatty acid biosynthesis proteins and the downregulation of adenosylhomocysteinase protein, glycolytic pathway enzymes, nitrogen assimilation enzymes, oxidative stress enzymes, and methionine-tRNA ligase(Castander-Olarieta et al, 2021). Similarly, in chickpea (Cicer arietinum L.), HS led to the differential expression of various proteins, including HSP70, ribulose bisphosphate carboxylase/oxygenase activase, plastocyanin oxidase and protoporphyrinogen oxidase, alongside the up-regulation of proteins related to defense, transport, intracellular traffic, and protein biosynthesis(Makonya et al, 2021).Wang et al (2021) reported 1,591 differentially abundant proteins (DAPs) related to stimuli response, structural molecule activity and transporter activity, catalytic activity, energy production and conversion, and carbohydrate transport and metabolism in two pepper varieties (heat-tolerant 17CL30 and heat-sensitive 05S180) upon HS exposure (40 C). In wheat under HS, Chunduri et al (2021) reported enhanced expression of DAPs involved in translation, gliadins, and low-molecular-weight glutenins and decreased expression of defenserelated, photosynthesis, glycolysis, and high-molecular-weight glutenins DAPs.…”
mentioning
confidence: 99%
“…Regarding heat stress, Makonya et al [ 144 ] identified an up-regulation in proteins related to protein synthesis, intracellular traffic, defense, and transport in the heat-tolerant genotype (Acc#7). Among the proteins are sucrose-phosphate synthase, sucrose-phosphate phosphatase, HSP70, ribulose bisphosphate carboxylase/oxygenase activase, plastocyanin, and protoporphyrinogen oxidase, which have a role in heat tolerance at the flowering growth stage.…”
Section: Breeding Approaches In Chickpeamentioning
confidence: 99%